The lucky one - Sparks, Nicholas (New York : Grand Central Pub., 2012)
After coming into possession of a photograph of a woman he has never met, Logan Thibault experiences a chain of fortuitous events that causes him to regard the photograph as a lucky charm, a belief that prompts a search for the woman.
'Now a major motion picture'--Cover.
Keywords: American fiction; North Carolina -- Fiction; North Carolina -- Fiction